N,N′-Diphenyl-9,10-dioxo-9,10-dihydroanthracene-2,7-disulfonamide - Wei-Guan Yuan; Hong-Ling Zhang (Acta Crystallographica Section E, 2013)
The title molecule, C26H18N2O6S2, has an overall Z-shaped conformation, in which the benzene rings are inclined to the anthraquinone mean plane by 60.60 (9) and 50.66 (13)°. In the crystal, N—H...O and C—H...O hydrogen bonds link the molecules into layers parallel to the bc plane.